2005
DOI: 10.1007/s11199-005-1295-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Reactions to Academic Sexual Harassment: Effects of Individualist vs. Collectivist Culture and Gender of Participants

Abstract: Male and female university students from the United States, Canada, Germany, the Netherlands, Ecuador, Pakistan, the Philippines, Taiwan, and Turkey read a standardized scenario in which a male professor was accused of sexually harassing a female graduate student. Respondents from individualist countries judged the professor to be guilty of sexual harassment more often than did those from collectivist countries. Women rendered significantly more guilty judgments and assigned more severe punishments to the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 26 publications
2
48
2
3
Order By: Relevance
“…These findings are somewhat contrary to the findings on attitudes towards sexual harassment in collectivist cultures or non-western cultures (Sigal et al 2005) such as Sri Lanka. It is also said that in collectivist cultures public discussions of sexual harassment are rare (Sigal et al 2005) and that people are more ready to accuse the victim and hold her more responsibile the victim for the harassment that had occurred.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…These findings are somewhat contrary to the findings on attitudes towards sexual harassment in collectivist cultures or non-western cultures (Sigal et al 2005) such as Sri Lanka. It is also said that in collectivist cultures public discussions of sexual harassment are rare (Sigal et al 2005) and that people are more ready to accuse the victim and hold her more responsibile the victim for the harassment that had occurred.…”
Section: Resultscontrasting
confidence: 89%
“…It is also said that in collectivist cultures public discussions of sexual harassment are rare (Sigal et al 2005) and that people are more ready to accuse the victim and hold her more responsibile the victim for the harassment that had occurred. Collectivist cultures are also said to be concerned more about preserving harmony in society and to value the needs of society rather than individual rights.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Kısa et al (2002) found that the experience of sexual harassment negatively affects Turkish women's job quality. Sigal et al (2005), in another cross-cultural study including nine nations, showed that Turkish university students' tolerance of sexual harassment was higher than American, Canadian, German and Dutch students' tolerance levels. Furthermore, in terms of the coping strategies of sexual harassment, Wasti and Cortina (2002) found that Turks and Hispanics avoided harassers more than Anglos.…”
Section: Studies On Sexual Harassment In Turkeymentioning
confidence: 94%
“…Sexual harassment continues to be a problem in today's US workplace, therefore, 40 years after the Civil Rights Act. Furthermore, judging from recent scholarly interest in sexual harassment experiences and perceptions from non-US samples (e.g, DeSouza and Solberg 2003;Parish et al 2006;Sigal et al 2005), sexual harassment is a world-wide concern.…”
Section: Introductionmentioning
confidence: 99%